الإطار القانوني لحماية المستهلك الإلكتروني - النذير, قمرة (Université de M'sila, 2018)
The progress and development in the field of information and electronic communications through the Internet has revolutionized communications technology, with many transactions taking place through various electronic means. E-consumer protection is an urgent and necessary requirement, because the risk to which it is exposed is greater and faster than the traditional consumer, and therefore modern legislation in e-commerce tends to put the consumer on its list of priorities and this is because this trade is an information system that is traded from during which countless goods and services. The consumer remains the weakest link in the contractual process, and therefore must be protected from the risks of illegal exploitation when contracting, especially if the absence of legal legislation protecting the electronic consumer exposes him to technical errors when contracting or in misleading him by the seller who Deals with it through a virtual market, which may lead to the reluctance of the consumer to buy electronic, for fear of being exploited, stolen or defrauded from where he does not know.